Mango (Mangifera indica) germplasm screening against burl disease and its effect on fruit yield and quality - SARAN, P L; CHOUDHARY, S P; RAJPUT, K S (The Indian Journal of Agricultural Sciences, 2020)
The present field study was undertaken at ICAR-Directorate of Medicinal and Aromatic Plants Research, Anand, Gujarat during 2016-17 to know the susceptible germplasm of mango (Mangifera indica L.) to burl disease under western part of India. Burl is an outgrowth on main trunk and lower branches of mango tree, having different sizes and shapes. This study represents the results of a survey conducted on more than 200 mango germplasm against burl disease in Gujarat state of India. In the survey it was found that 20 mango germplasms were susceptible or express symptoms of burl disease. Highest incidence was observed in Mehmud Vikarabad, Arka Aruna, Badami Modal, Mankurad, Joshipura Junagadh, Elite Ditla and seedling from four locations (repositories). Maximum burl size was observed in Langra cultivar. Highest burl incidence, burl size and fruit yield loss were found at Pariya location with maximum relative humidity, temperature flux and rainfall. Age of tree also showed positive relationship with burl incidence, burl size and fruit yield loss in Langra. The burl infected tree fruits had maximum content of TSS, total sugar, reducing sugar, non-reducing sugar and ascorbic acid content as compared to non-infected fruit pulp, this may be due to change in sugar metabolism.